The Influence of Marketing Mix and Brand Image on the Decision to Choose Kindergarten Education in South Semarang: The Mediating Role of Parental Trust - Dila, Farah; Mulyani, Sri; Hidayat, Arif (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study analyzes the factors influencing parental decision-making when selecting a kindergarten (TK) in South Semarang, Indonesia. It examines the direct and indirect effects of the marketing mix—conceptualized through price, place, and physical evidence—and brand image on the school choice process, with trust hypothesized as a critical mediating variable. A quantitative approach was employed, utilizing a structured questionnaire distributed via WhatsApp to parents of kindergarten students. Data from 153 valid responses were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) with SmartPLS 4.0.0.9. The results confirm that both the marketing mix and brand image exert significant positive direct effects on parental trust and, subsequently, on the school decision-making process. Trust fully mediates the relationship between the marketing mix and decision-making and partially mediates the relationship between brand image and decision-making. Notably, brand image demonstrates the strongest direct influence on the final choice. The model explains a substantial proportion of variance in trust (65.8%) and in the decision-making process (67.8%). This research provides a nuanced, context-specific model for early childhood education (PAUD) marketing within a developing urban setting.